2014
DOI: 10.1523/jneurosci.0718-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Dopamine Depletion Upregulates Caudate Dopamine and Alters Behavior via Changes in Reinforcement Sensitivity

Abstract: Schizophrenia is associated with upregulation of dopamine (DA) release in the caudate nucleus. The caudate has dense connections with the orbitofrontal cortex (OFC) via the frontostriatal loops, and both areas exhibit pathophysiological change in schizophrenia. Despite evidence that abnormalities in dopaminergic neurotransmission and prefrontal cortex function co-occur in schizophrenia, the influence of OFC DA on caudate DA and reinforcement processing is poorly understood. To test the hypothesis that OFC dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 60 publications
0
50
0
Order By: Relevance
“…Based on our earlier study (Kahnt et al, 2012), anatomical tracing work in primates (Carmichael and Price, 1996;Ongür and Price, 2000), and the results of a meta-analytic connectivity modeling study (Zald et al, 2014), we focused on the parcellations with 2 and 6 subdivisions. The par- Anatomical labels, MNI coordinates (x, y, z), z-scores, and cluster size (number of voxels) for whole-brain connectivity of individual OFC subregions in the K2 parcellation contributing to the separation between groups, thresholded at p Ͻ 0.05, Bonferroni corrected (z Ͼ 4.47) and k Ͼ 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our earlier study (Kahnt et al, 2012), anatomical tracing work in primates (Carmichael and Price, 1996;Ongür and Price, 2000), and the results of a meta-analytic connectivity modeling study (Zald et al, 2014), we focused on the parcellations with 2 and 6 subdivisions. The par- Anatomical labels, MNI coordinates (x, y, z), z-scores, and cluster size (number of voxels) for whole-brain connectivity of individual OFC subregions in the K2 parcellation contributing to the separation between groups, thresholded at p Ͻ 0.05, Bonferroni corrected (z Ͼ 4.47) and k Ͼ 2.…”
Section: Discussionmentioning
confidence: 99%
“…It receives highly processed input from every sense, and is connected to other prefrontal areas, premotor cortex, and subcortical areas such as the striatum, amygdala, hippocampus, and hypothalamus (Morecraft et al, 1992;Cavada et al, 2000). This dense connectome suggests that functional interactions with other brain regions are key to the processes that are performed by the OFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Bari and colleagues (2010) demonstrated the effects of different serotonergic (5-HT) manipulations on sensitivity of rats to feedback in the PRL paradigm. Two years later, Ineichen and colleagues (2012) investigated the role of 5-HT on feedback sensitivity in mice, and recently, the PRL paradigm has been employed to investigate the roles of 5-HT and DA in feedback-based decision making in non-human primates (marmosets) (Clarke et al, 2014;Rygula et al, 2015a). It is worth noticing that in the present study we used an operant PRL paradigm with a real punishment (mild foot-shock) for the first time, as opposed to only a lack of reward, as has been used in the previous studies with rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the loss of a DA Value signal in the orbital PFC decreased the ability of these neurons to generate representations of reward needed to guide reinforcementdirected behavior. A more recent study has shown that depletion of DA in the orbital PFC also leads to increased tonic DA levels in caudate, which may contribute as well (Clarke et al, 2014). Given the importance of DA to reward signaling, the importance of orbital and medial PFC circuits in guiding behavior based on reward, the elaboration of these PFC areas in primates, and their relationship to mood disorders, this seems a particularly rich arena for future exploration.…”
Section: Dopamine Effects On the Orbital Prefrontal Cortexmentioning
confidence: 99%